The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.7150/thno.51193
|View full text |Cite
|
Sign up to set email alerts
|

Combination of long-acting TRAIL and tumor cell-targeted photodynamic therapy as a novel strategy to overcome chemotherapeutic multidrug resistance and TRAIL resistance of colorectal cancer

Abstract: Chemotherapeutic multidrug resistance (MDR) is the major hindrance for clinical therapy of colorectal cancer (CRC). Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) with selective cytotoxicity might overcome MDR of CRC cells. Unfortunately, cross-resistance to TRAIL has been detected in many CRC cells, suggesting the need to combine TRAIL with sensitizers to combat refractory CRC. Our purpose is to explore the potential of combination therapy of TRAIL and tumor-cell targeted photodynamic therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…In this regard, TRAIL as a capable chemotherapeutic ingredient has attracted considerable attention; however, TRAIL therapy has faced some limitations in the clinical setting. Although the exact mechanisms contributing to the escape from TRAIL-induced apoptosis and progress of resistance to TRAIL in tumor cells has not yet been found completely, it seems that down-regulating pro-apoptotic proteins and DR4/5, concomitant with up-regulating anti-apoptotic proteins along with activating some signaling axis plays an influential role in this regard ( 225 , 226 ). Nonetheless, it is still not elucidated whether the cellular procedures alone or in combination can stimulate resistance to TRAIL.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, TRAIL as a capable chemotherapeutic ingredient has attracted considerable attention; however, TRAIL therapy has faced some limitations in the clinical setting. Although the exact mechanisms contributing to the escape from TRAIL-induced apoptosis and progress of resistance to TRAIL in tumor cells has not yet been found completely, it seems that down-regulating pro-apoptotic proteins and DR4/5, concomitant with up-regulating anti-apoptotic proteins along with activating some signaling axis plays an influential role in this regard ( 225 , 226 ). Nonetheless, it is still not elucidated whether the cellular procedures alone or in combination can stimulate resistance to TRAIL.…”
Section: Discussionmentioning
confidence: 99%
“…DR5 has been found upregulated in various types of tumors, including colorectal carcinomas, and can be exploited for selective apoptotic killing of cancer cells through caspase 8 [ 52 ]. Recent studies have shown that PDT extensively sensitizes refractory colon tumors to death signals delivered by long-acting TRAIL [ 53 ], possibly by increasing the levels of TRAIL receptors on tumor cells. Furthermore, the increased levels of the BID transcripts evidenced by us may sustain the connection of death receptor signaling to the mitochondrial apoptotic machinery [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The high affinity (pM to nM range) of the affibody molecules to their targets, their small size (in vivo this results in fast clearance from the circulation with mostly renal excretion), and good tumor penetration make them ideal targeting agents to increase the concentration of the photosensitizers in the tumor site, while limiting toxicity in normal tissues. The photosensitizer IR700DX (IR700) was conjugated to the ZEGFR affibody (Ze), which has high specificity and affinity for EGFR to produce the Ze-IR700 conjugate [229] (Table 12). Ze-IR700 conjugates bind to EGFR-overexpressing cells and are uptaken, localizing predominantly in lysosomes [229].…”
Section: Anti Egfr-affibodiesmentioning
confidence: 99%
“…The photosensitizer IR700DX (IR700) was conjugated to the ZEGFR affibody (Ze), which has high specificity and affinity for EGFR to produce the Ze-IR700 conjugate [229] (Table 12). Ze-IR700 conjugates bind to EGFR-overexpressing cells and are uptaken, localizing predominantly in lysosomes [229]. The in vitro phototoxicity of the Ze-IR700 conjugate was demonstrated, suggesting that PDT treatment predominantly induces lysosome-associated apoptosis [229].…”
Section: Anti Egfr-affibodiesmentioning
confidence: 99%